Antifungal activity of eicosanoic acids isolated from the endophytic fungus Mycosphaerella sp. against Cryptococcus neoformans and C. gattii. (November 2016) - Pereira, Cristiane Bigatti; Pereira de Sá, Nívea; Borelli, Beatriz Martins; Rosa, Carlos Augusto; Barbeira, Paulo Jorge Sanches; Cota, Betania Barros; Johann, Susana
Abstract: The antifungal effects of two eicosanoic acids, 2-amino-3, 4-dihydroxy-2-25-(hydroxymethyl)-14-oxo-6, 12-eicosenoic acid (compound1 ) and myriocin (compound2 ), isolated from Mycosphaerella sp. were evaluated against Cryptococcus neoformans and C. gattii. The compounds displayed antifungal activities against several isolates of C. neoformans and C. gattii, with minimal inhibitory concentration (MIC) values ranging from 0.49 to 7.82 μM for compound1 and 0.48–1.95 μM for compound2 . In the checkerboard microtiter test, both compounds exhibited synergistic activity with amphotericin B against C. gattii . Ultrastructural analysis revealed several signs of damage in C. gattii and C. neoformans cells treated with compounds1 and2, including deformities in cell shape, depressions on the surface, and withered cells. The cells of C. gattii treated with compounds1 and2 showed less loss of cellular material in comparison to those treated with amphotericin B. The difference in cellular material loss increased in a test compound concentration-dependent manner. Consistent with this observation, compounds1 and2 were able to internalize propidium iodide (PI) in C. gattii cells. In addition, compound2 induced the formation of several pseudohyphae, suggesting that it could reduce virulence in C. gattii cells. The study results show that these natural products led to membrane damage; however, this may not be the main target of action. These compounds have potential antifungal activity and could be useful in further studies for developing more effective combination therapies with amphotericin B and reducing side effects in patients. Highlights: The two compounds led to membrane damage in Cryptoccus gatti and C. neoformans . Myriocin induced the formation of several pseudohyphae in C. gattii . The two compounds exhibited synergistic activity with amphotericin B against C. gattii .